Paternity in wild ring‐tailed lemurs (Lemur catta): Implications for male mating strategies. Issue 12 (8th July 2016) - Parga, Joyce A.; Sauther, Michelle L.; Cuozzo, Frank P.; Youssouf Jacky, Ibrahim Antho; Lawler, Richard R.; Sussman, Robert W.; Gould, Lisa; Pastorini, Jennifer
Abstract : In group‐living species with male dominance hierarchies where receptive periods of females do not overlap, high male reproductive skew would be predicted. However, the existence of female multiple mating and alternative male mating strategies can call into question single‐male monopolization of paternity in groups. Ring‐tailed lemurs ( Lemur catta ) are seasonally breeding primates that live in multi‐male, multi‐female groups. Although established groups show male dominance hierarchies, male dominance relationships can break down during mating periods. In addition, females are the dominant sex and mate with multiple males during estrus, including group residents, and extra‐group males—posing the question of whether there is high or low male paternity skew in groups. In this study, we analyzed paternity in a population of wild L. catta from the Bezà Mahafaly Special Reserve in southwestern Madagascar. Paternity was determined with 80–95% confidence for 39 offspring born to nine different groups. We calculated male reproductive skew indices for six groups, and our results showed a range of values corresponding to both high and low reproductive skew. Between 21% and 33% of offspring (3 of 14 or three of nine, counting paternity assignments at the 80% or 95% confidence levels, respectively) were sired by extra‐troop males. Males siring offspring within the same group during the same year appear to be unrelated. Our study provides evidence of varying male reproductive skew in different L. catta groups. A single male may monopolize paternity across one or more years, while in other groups, >1 male can sire offspring within the same group, even within a single year. Extra‐group mating is a viable strategy that can result in extra‐group paternity for L. catta males.